2016
DOI: 10.2136/vzj2015.08.0115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Direct‐Coupled Time‐Domain Reflectometry for Determination of Soil Water Content and Bulk Electrical Conductivity

Abstract: Signal degradation in coaxial cables and interconnects is a long-standing problem in the practical deployment of time-domain reflectometry (TDR) for soil water monitoring. Acclima, Inc. has recently commercialized a TDR sensor (TDR-315) with all electronics required for waveform acquisition embedded in the probe head. We calibrated ten TDR-315 sensors and conventional TDR for apparent permittivity (K a ) and bulk electrical conductivity (s a ) measurements. Also, soil water content calibrations were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 26 publications
0
46
0
1
Order By: Relevance
“…Each of these sensors measures a property that is related to soil permittivity, which in turn is positively associated with θ v . TDR315 is a time domain reflectometer that generates its own EM pulses and analyzes its own waveforms to obtain travel times (Schwartz et al, 2016). CS616 and CS655 are both water content reflectometers that count the average times per second the reflection of the previous generated EM pulse returns to the sensor head to trigger the next generated EM pulse (Seyfried and Murdock, 2001;Kelleners et al, 2005).…”
Section: Sensorsmentioning
confidence: 99%
“…Each of these sensors measures a property that is related to soil permittivity, which in turn is positively associated with θ v . TDR315 is a time domain reflectometer that generates its own EM pulses and analyzes its own waveforms to obtain travel times (Schwartz et al, 2016). CS616 and CS655 are both water content reflectometers that count the average times per second the reflection of the previous generated EM pulse returns to the sensor head to trigger the next generated EM pulse (Seyfried and Murdock, 2001;Kelleners et al, 2005).…”
Section: Sensorsmentioning
confidence: 99%
“…The impact of soil salinity on sensor readings of soil volumetric water content ( θ v ) (m 3 m −3 ) has been highlighted in several studies [ 15 , 16 , 17 ]. For example, Wyseure et al [ 16 ] reported that θ v error was acceptable at soil bulk electricity conductivity (EC) (dS m −1 ) levels below 2.0 dS m −1 , and Schwartz et al [ 18 ] found that θ v estimates were not affected at bulk EC levels below 2.8 dS m −1 . These thresholds are exceeded in many irrigated areas in arid/semi-arid regions, where there is a great need for improving irrigation management using sensor technologies.…”
Section: Introductionmentioning
confidence: 99%
“…3, right), which can automatically guide the irrigation system or be modified by the irrigation manager before automatic applica- tion. The infrared sensors and sensor network were commercialized from research prototypes (O'Shaughnessy et al, 2013), and the soil water sensors were also developed with a commercial partner (Evett et al, 2015;Schwartz et al, 2016). This amounts to a 3R concept for irrigation (right place, right amount, and right time) and results in improved crop water productivity for several field crops in the U.S. Great Plains (cotton, maize, sorghum, and soybean) (O'Shaughnessy et al, 2016).…”
Section: Prescription Irrigationmentioning
confidence: 99%